2019
DOI: 10.1016/j.pedneo.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and nutritional outcome of pediatric esophageal stenosis with endoscopic balloon dilatation

Abstract: EBD has good long-term clinical success and nutritional promotion in pediatric patients with esophageal stricture, especially in short segment stricture or stricture in the middle esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 24 publications
4
21
0
Order By: Relevance
“…Retrospective reviews have reported up to 33 balloon procedures in a single patient, and a ten‐year retrospective review in the UK found that 148/166 patients (89%) required multiple balloon procedures . In our study, 56% of patients (33/59) had multiple balloon procedures to maintain the airway.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Retrospective reviews have reported up to 33 balloon procedures in a single patient, and a ten‐year retrospective review in the UK found that 148/166 patients (89%) required multiple balloon procedures . In our study, 56% of patients (33/59) had multiple balloon procedures to maintain the airway.…”
Section: Discussionmentioning
confidence: 47%
“…Overall procedural success and clinical outcomes for all balloon dilatation patients (n = 59) using follow-up from the Airway Intervention Registry and administrative data from Hospital Episodes Statistics Retrospective reviews have reported up to 33 balloon procedures in a single patient, 13 and a ten-year retrospective review in the UK found that 148/166 patients (89%) required multiple balloon procedures. 14 In our study, 56% of patients (33/59) had multiple balloon procedures to maintain the airway.…”
Section: F I G U R Ementioning
confidence: 99%
“…Achieving sufficient food intake is the target of esophageal dilatation in patients with esophageal stricture [ 8 ]. If left untreated, patients with esophageal stricture may suffer from failure to thrive and can develop serious complications [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al reported a 5year retrospective study on 50 pediatric patients showing an overall clinical success rate of EBD therapy as high as 72% with emphasis of significantly increased weight-for-age z scores in all the patients receiving EBD, particularly in those with short strictures and strictures in the middle esophagus. 7 This report is the first to correlate long-term nutritional outcomes in weight-for-age z scores with the location and length of esophageal strictures, 7 rather than evaluating patients only with BMI as well as variations in the z scores of weight and height. 3,6 Whether different etiologies correlate with clinical outcomes and effectiveness of EBD for esophageal strictures in children remains obscure and requires additional studies for clarification.…”
mentioning
confidence: 99%
“…8 Chang et al claimed higher clinical success rates of EBD in patients with esophageal atresia than those with corrosive injury by statistical analysis from not all but a part of the enrolled patients. 7 Timing of EBD treatment and severity of corrosive injury should be considered in future studies. Moreover, we anticipated further research on advanced therapies (e.g., intralesional steroid injection or topical Mitomycin C) as rescue adjuncts to treat patients with recurrent or refractory esophageal strictures resistant to EBD therapy.…”
mentioning
confidence: 99%